Animation in process. - Selby, Andrew (Laurence King Pub., 2009)
From Hollywood blockbuster to striving independent filmmaker, from mobile phone games to characters advertising products on television, from pseudo live action through to virtual environments, animation is able to transcend boundaries to new audiences. This title explores working methods and processes used by some of the best animators.